Afrocentroamericaneidades: dislocación del istmo y translocación caribeña y diaspórica - Muñoz Muñoz, Marianela (2019)
This article offers a panoramic revision of the complex relationships between Black populations, the Caribbean space, and the Central American isthmus from the Colony to the present. As a framework for this analysis, I explore the concept of AfroCentral Americanness, as a simultaneous circumstance of geographical, cultural and political dislocation and translocation. On the one hand, Central American countries exclude both the space and Afro-Central American identities from their repertoires of nationhood. On the other, these populations define themselves through a linkage with the insular Caribbean since the colonial times. They affirm a Circum-Caribbean experience during the (liberal) plantations era. They also capitalize their Afro-Latino condition through the migrations to the United States and other territories in the region, from the mid-twentieth century until today. Entangled with the formation and mobilization of diasporic identities, Afro-Central Americanness speaks about the cultural malleability (and fragility) of national borders. It also suggests dynamic projects challenging the mestizo (or white) Central American imaginaries and the possibilities of articulation within.